Kusta Tipe Multibasiler dengan Erythema Nodosum Leprosum Selama Pengobatan Disertai Diabetes Melitus Tipe 2 dan Anemia - Ary Fadhil Maulana; Muhammad Mimbar Topik (Jurnal Ilmu Kesehatan dan Gizi, 2026)
Leprosy is a chronic infectious disease caused by Mycobacterium leprae, an obligate intracellular bacterium that affects the skin, peripheral nerves, upper respiratory mucosa, and eyes. Type 2 diabetes mellitus (T2DM) is a comorbidity that can worsen the course of leprosy. The female patient, Mrs. D, aged 55 years came to the emergency room of Cut Meutia Hospital with the main complaint of red bumps accompanied by pain on the face, hands, chest, and back since 3 days ago and additional complaints such as fever, joint pain, and numbness and loss of feeling in the legs, weakness, frequent thirst, and frequent urination. Dermatologic status is obtained in the facial region in the form of erythema nodules with firm boundaries with numular size, multiple. Laboratory examination showed anemia and leukocytosis. The therapy given was MDT MB package, ferrous sulfate 1x325 mg and PRC transfusion 3 kolf. Complaints arose acutely after the patient resumed taking MDT (multidrug therapy) leprosy drugs which had previously been stopped for more than 3 months. Based on the time of onset of symptoms, history of leprosy treatment, and the manifestation of systemic inflammatory lesions with signs of neurotropism, it can be suspected that the patient is experiencing a type 2 leprosy reaction or Erythema Nodosum Leprosum (ENL).